Influence of blowing agent on the fresh- and hardened-state properties of lightweight geopolymers. (15th October 2016) - Novais, Rui M.; Ascensão, G.; Buruberri, L.H.; Senff, L.; Labrincha, J.A.
Abstract: The production of lightweight geopolymers is an emergent area, and the influence of the pore forming agent on geopolymer kinetics and the rheology of the pastes has been rather neglected up to now. In this work the influence of the blowing agent content, NaOH molarity and water content on the fresh and hardened-state properties of fly ash-containing geopolymers was evaluated. Results demonstrate that the blowing agent decreases the slurries yield stress, which extends the open time before in situ application. It was also found that the geopolymerisation rate is only slightly affected by the blowing agent, while a strong impact is exerted by the activator molarity. The proper association between NaOH molarity and blowing agent content leads to the production of lightweight geopolymers exhibiting very low thermal conductivity (up to 0.08 W/m K) and apparent density (440 kg/m 3 ). The thermal conductivity shown by these innovative materials suggest their suitability for thermal insulating applications. Graphical abstract: Highlights: The dominant factors affecting the fresh- and hardened-state properties of lightweight geopolymers were investigated. Geopolymers exhibiting very low thermal conductivity (up to 0.08 W/ m K) and apparent density (440 kg/m 3 ) were produced. Thermal conductivity values exhibited by these geopolymers suggest their use in thermal insulating applications. The incorporation of biomass fly ash waste mitigates the environmental problems associated with this waste disposal.